A study of scrub meningoencephalitis and keeping it as a common differential diagnosis - Patwardhan, Bhalachandra; Chaudhary, Ritu; Mathur, Rajendra Dutt (International Journal of Research in Medical Sciences, 2022)
Background: Scrub typhus is caused by the organism Orientia tsutsugamushi, transmitted by trombiculid mites. Meningoencephalitis as a cause of mortality in cases of scrub typhus is becoming a common entity now. Aims and objectives were to study the incidence of meningoencephalitis in scrub typhus cases admitted to our hospital and stress the importance of keeping it as a common differential diagnosis. Methods: A descriptive observational study of 39 diagnosed cases of scrub typhus admitted to our hospital for 6 months duration (May 2018 to October 2018) was conducted. Data concerning the cases were recorded and analyzed using appropriate statistics. Results: Out of 39 cases admitted, 8 patients were diagnosed as having meningoencephalitis. Patients with meningoencephalitis had severe thrombocytopenia when compared to those without any central nervous system (CNS) symptoms. All patients responded well to doxycycline therapy with no mortality amongst cases under study. Conclusions: There have been numerous outbreaks of scrub typhus in our state of Rajasthan, especially in the Hadoti region. And in recent years, scrub typhus has been an important contributor to the newer class of emerging infections causing mortality in India. Meningoencephalitis although rare forms a major part of the complications of scrub typhus.